Small Intestinal Bacterial Overgrowth Affects the Responsiveness to Colchicine in Familial Mediterranean Fever - E. Verrecchia; L. L. Sicignano; M. La Regina; G. Nucera; I. Patisso; L. Cerrito; M. Montalto; A. Gasbarrini; R. Manna (Mediators of Inflammation)
Objective. Familial Mediterranean fever (FMF) is an autosomal recessive disease due to a MEFV gene mutation. Since Helicobacter pylori infection has been described to increase the severity and frequency of FMF attacks, we evaluate if overgrowth of small intestinal bacterial (SIBO), associated with a release of bacterial products, can affect the response to colchicine in FMF patients poorly responsive to colchicine. Methods. We revised our Periodic Fever Centre database to detect FMF patients who were poorly responsive to colchicine, without a well-defined cause of drug resistance. They were evaluated for SIBO presence, then treated with decontamination therapy. Results. Among 223 FMF patients, 49 subjects show colchicine resistance, and no other known causes of colchicine unresponsiveness has been found in 25 patients. All 25 patients underwent glucose breath test; 20 (80%) of them were positive, thus affected by SIBO. After a successful decontamination treatment, 11 patients (55%) did not show FMF attacks during the following three months (p<0.01), while 9 of them revealed a significant reduction of the number of attacks compared to three months before (p<0.01). Conclusion. The SIBO eradication improves laboratory and clinical features of FMF patients. Thus, patients with unresponsiveness to colchicine treatment should be investigated for SIBO.